enetic parameter for first lactation and lifetime performance traits in crossbreed cattle - SINGH, V K; SINGH, C V; KUMAR, D; SHARMA, R J (The Indian Journal of Animal Sciences, 2011)
The data for the present investigation were obtained from the performance records of 1085 crossbred daughters belonging to 7 different genetic groups and by 57 of bulls maintained at Dairy Fann ofG B.Pant University ofAgriculture and Technology, Pantnagar, during 1974-2004 were used to estimate genetic parameters of first lactation and life time performance traits. The averages of AFe, FLMY, FLP, FDP, FCI, HL, TLL and LTMYwere found as 1371.06±15.49 days, 3064.74±49.40 liter, 356.63±5.l2days, 172.85±7.23 days, 529.48±8.51 days, 1653.54±26.06 days, 1338.64±26.50 days and 8931.46±154.49 liter, respectively. The heritability estimates for the corresponding traits were 0.12±0.06, O.12±0.060, O.l8±0.07, O.09±O.06, O.09±O.06, O.lO±O.06, O.12±0.06 and O.07±O.05 by LSA method and the heritability estimates of the corresponding traits found as 0.24±O.08, O.23±O.08, O.22±O.07, 0.12±O.07, O.14±O.07, O.12±O.06, O.13±O.06 and O.14±O.06, respectively. The estimates of heritability for fITst lactation and lifetime traits from DFREML analysis were higher and significant than least square analysis method. These difference in h2 estimation revealed that sire model ignores both the dams of cow (sire's mate) and relationship between females while DFREML evaluate both the sires and cows simultaneously. APC had positive genetic correlation with all other fITst lactation traits except with FLP. FLMY had positive genetic and phenotypic correlations with all other first lactation traits and values varied from low to medium. These results suggested that selection on the basis of FLMY would be expected to improve lifetime performance traits.